PUBLIC SERVICE TRANSFORMATION: THE IMPLEMENTATION OF PTSP IN CLASS 1A OF THE PALU RELIGIOUS COURT - Rahmatullah, Nursalam; Asmarini, Andini (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2024)
PTSP is an innovation in the bureaucratic system designed to improve efficiency, transparency, and accountability of services to the public. In this case, the Supreme Court, through the Director General of Religious Courts, has stipulated the Director General of Badilag's decree No. 1403.b concerning guidelines for one-stop integrated services in the Religious Courts. Therefore, this study aims to analyze the transformation of public services through implementing One-Stop Integrated Services (PTSP) in Religious Courts, specifically in Palu Religious Court with Class 1A status, which should be an example of other Religious Courts with lower classes. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, observation, and document analysis. The results showed that implementing PTSP in Palu Religious Court Class 1A has brought significant changes in various aspects of public services. Service time has become faster, procedures have become more straightforward, and public satisfaction with services has increased. However, this study also found several obstacles in the implementation of PTSP: first, the infrastructure that is not yet optimal; second, the unavailability of bank officers at any time; and third, the malfunction of the PTSP Online service system due to the need for periodic upgrading and system development.